Evaluation of cases of mammoplasty with the areolar inferior pedicle technique - Eduardo Favarin; Glayse June Sassaki Favarin; Ives Alexandre Yutani Koseki; Fábio Yutani Koseki (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Mammoplasty is one of the most common plastic surgeries in Brazil. Among the surgical techniques described in the literature, the areolar inferior pedicle technique is the most significant because of its versatility, safety, and satisfactory aesthetic results. This study avaluated cases of mammoplasty with the areolar inferior pedicle technique performed by the author, and to propose a small change in the attachment of the pedicle to the pectoralis major muscle. METHODS: A total of 74 patients underwent the surgery from June 2007 to December 2014. RESULTS: The average patient age was 35.63 years; the mean body mass index was 25.8; and the mean follow-up duration was 28 months. Complications occurred in 33.76% of the cases, and the average amount of resected tissue was 585 g. The degree of satisfaction was excellent or good in 93% of the cases. The sensitivity of the areolar-papillary complex (APC) was maintained in 72% of left-breast reconstructions and 77% of right-breast reconstructions. Moreover, there was a complete loss of sensitivity in 3% of left-breast cases. CONCLUSION: The use of mammoplasty with the areolar inferior pedicle was versatile and safe, and produced favorable outcomes. In addition, the sensitivity of the APC was adequately maintained. Further studies might confirm the importance of the change in fixation of the pedicle suggested in this study.